Preparation of micro/nanopatterned gelatins crosslinked with genipin for biocompatible dental implants - Makita, Reika; Akasaka, Tsukasa; Tamagawa, Seiichi; Yoshida, Yasuhiro; Miyata, Saori; Miyaji, Hirofumi; Sugaya, Tsutomu (Beilstein Journal of Nanotechnology, 2018)
Background: Collagen is a basic component of the periodontium and plays an important role in the function of the periodontal unit. Therefore, coating with collagen/gelatin has been applied to enable dental implants to positively interact with peri-implant tissues. Although the micro/nanoscale topography is an important property of the surface of dental implants, smaller collagen/gelatin surface patterns have not been sufficiently developed. Furthermore, only few reports on the behavior of cells on gelatin surfaces with different patterns and sizes exist. In this study, we developed micro/nanometer-scaled gelatin surfaces using genipin crosslinking, with the aim of understanding the use of patterning in surface modification of dental implants.Results: Grooves, holes, and pillars, with widths or diameters of 2 µm, 1 µm, or 500 nm were fabricated using a combination of molding and genipin crosslinking of gelatin. The stability of the different gelatin patterns could be controlled by the degree of genipin crosslinking. The gelatin patterns at 20 mM concentration of genipin and 41% crosslinking maintained a stable, patterned shape for at least 14 days in a cell culture medium. A cell morphology study showed that the cells on groves were aligned along the direction of the grooves. In contrast, the cells on pillars and holes exhibited randomly elongated filopodia. The vinculin spots of the cells were observed on the top of ridges and pillars or the upper surface of holes. The results of a cell attachment assay showed that the number of surface-attached cells increased with increasing patterning of the gelatin surface. Unlike the cell attachment assay, the results of a cell proliferation assay showed that Saos-2 cells prefer grooves with diameters of approximately 2 µm and 1 µm and pillars with diameters of 1 µm and heights of 500 nm. The number of cells on pillars with heights of 2 µm was larger than those of the other gelatin surface patterns tested.Conclusion: These data support that a detailed design of the gelatin surface pattern can control both cell attachment and proliferation of Saos-2 cells. Thus, gelatin surfaces patterned using genipin crosslinking are now an available option for biocompatible material patterning.
Keywords: cell attachment; cell proliferation; dental implants; gelatin; genipin; nanopatterning